Personal Hygiene and Early Mobilization with Perineum Wound Healing - Aidha Rachmawati; Diah Jerita Eka Sari; Nourma Yunita (JURNAL KEBIDANAN, 2019)
Postpartum mothers who have perineal wounds are susceptible to infection because they are not clean and will affect the length of healing of the perineum. Early mobilization is a policy to quickly guide postpartum mothers out of their beds and walk and can smooth blood flow so as to accelerate the healing of perineal wounds. Perineal wounds due to rupture or laceration are areas that are not easy to keep clean and dry. If healing of wounds is not handled properly it will cause imperfect rupture wound healing. Perineal rupture is a birth canal injury that occurs at the time of the baby's birth, either using or not using a tool. The aim was to determine the relationship of personal hygiene and early mobilization with healing of perineal wounds on postpartum 7th day mothers in Pasanggar Pamekasan Village. Method Analytic, cross-sectional, purposive sampling, population of 38 postpartum mothers, 34 samples of postpartum mothers.The results of the study good day-to-day personal hygiene of postpartum mothers (67.6%), good early mobilization (61.8%), good perineal wound healing (58.8%), good personal hygiene, good perineal wound healing (87 %), early mobilization of good perineal wound healing is good (76.2%). Rank Spearman test, personal hygiene with perineal wound healing p = 0,000 α 0,05 and mobilization with wound healing p = 0,002 α 0,05 means that there is a significant relationship. Conclusion there is a relationship between personal hygiene and early mobilization with healing of perineal wounds in postpartum mothers on the 7th day.